Synthesis and Characterization of Bioglass 45S Doped with Ag - Vuong, Bui Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4692, 2018)
The bioglass 45S doped with Ag (45S-Ag) was successful synthesized by melting method. The influence of doping Ag on the glass matrix was highlighted by DTA method. XRD analysis confirmed the amorphous structure of synthetic glass. The presence of Ag element was controled by EDX analysis. ‘‘In vitro’’ of synthesized glass was effectuated by soaking of glass powder in SBF solution. EDX result indicated that silver was released when immersing derivative bioglass in SBF solution and silver is an antibacterial agent. XRD and SEM confirmed the bioactivity of glass 45S-Ag by the apatite formation on its surface. Keywords Bioglass, bioactivity, Ag, 45S-Ag, melting, SBF References 1. L. L. Hench, Journal of the American Ceramic Society 74 (1991) 1487-1510. 2. L. L. Hench L.L, Journal of Materials Science: Materials in Medicine 17 (2006) 967-978. 3. I. Ahmed, D. Ready, M. Wilson, and J. C. Knowles, J. Biomed. Mater. Res 79 (2006) 618-626. 4. R. O. Becker, Met. Based Drugs 6 (1999) 311-314. 5. T. Kokubo, H. Kushitani, S. Sakka, T. Kitsugiand T. Yamamuro, Journal of Biomedical Materials Research, 24 (1990) 721-734. 6. T. Kokuboand H. Takadama, Biomaterials, 24 (2006) 2907-2915. 7. Fiche JCPDF 09-432. 8. E. Dietrich, H. Oudadesse, A. Lucas-Girot A and M. Mami, Journal of Biomedical Materials Research, 88A (2008) 1087-1096.